Can remote sensing enable a Biomass Climate Adaptation Index for agricultural systems? - Ferguson, Amy; Murray, Catherine; Tessema, Yared Mesfin; McKeown, Peter C.; Reymondin, Louis; Loboguerrero Rodriguez, Ana María; Talsma, Tiffany; Allen, Brenden; Jarvis, Andy; Golden, Aaron; Spillane, Charles (Frontiers Media, 2022)
Systematic tools and approaches for measuring climate change adaptation at multiple scales of spatial resolution are lacking, limiting measurement of progress toward the adaptation goals of the Paris Agreement. In particular, there is a lack of adaptation measurement or tracking systems that are coherent (measuring adaptation itself), comparable (allowing comparisons across geographies and systems), and comprehensive (are supported by the necessary data). In addition, most adaptation measurement efforts lack an appropriate counterfactual baseline to assess the effectiveness of adaptation-related interventions. To address this, we are developing a “Biomass Climate Adaptation Index” (Biomass CAI) for agricultural systems, where climate adaptation progress across multiple scales can be measured by satellite remote sensing. The Biomass CAI can be used at global, national, landscape and farm-level to remotely monitor agri-biomass productivity associated with adaptation interventions, and to facilitate more tailored “precision adaptation”. The Biomass CAI places focus on decision-support for end-users to ensure that the most effective climate change adaptation investments and interventions can be made in agricultural and food systems.